AMANAH DALAM PERSPEKTIF AL-QUR’AN - Muh. Tang S (AZKIYA, 2022)
Trust is one of the most basic building blocks in interacting with God, humanity, the environment, and oneself. God entrusts only to humans, because only they are capable of carrying it out. To implement this trust, humans must perform their worship to Allah, both mandatory and non-mandatory worship, and trust involves not only material matters but also physical matters. Fulfilling the rights of Allah is a trust, doing good to other people is a trust, taking care of, educating, and supporting one's family, children, and wife is a trust, so all human affairs are trusts that have been entrusted by Allah, therefore human life is given the responsibility of trust that must be accounted for in the hereafter